Encyclopedia of genetics (Fitzroy Dearborn, 2001)
This one-volume text covers the field of genetics from Gregor Mendel's experiments in 1854 to current advances in genomics. Surprisingly absent from the preliminary section, "Introducing Genetics," is a discussion of James Watson and Francis Crick's 1953 discovery of the DNA double helix, which is a major oversight